2021
DOI: 10.3390/ijerph182212237
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health Situation of 12-Year-Old School Children in the Rural Region of Ilembula in Southwestern Tanzania: A Cross-Sectional Study

Abstract: There has been no research on the prevalence of and factors associated with dental caries in rural southwestern Tanzania among schoolchildren. Determining the prevalence of and factors associated with dental caries will help to assess the need for dental intervention and prophylactic measures among children in the region. In February 2020, a cross-sectional study was conducted in the Wanging’ombe District of the Ilembula Ward. The data were collected through clinical examinations and personal interviews at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…This should begin at the time of the eruption of the primary teeth. When fluoride toothpaste is used, brushing the teeth can help to deliver fluoride to the tooth surfaces, which can help to keep the teeth clean [ 44 , 45 , 46 , 47 ]. The results of the present study suggested that tooth brushing habit is one of the significant factors that can have an effect on the dmft scores of the child.…”
Section: Discussionmentioning
confidence: 99%
“…This should begin at the time of the eruption of the primary teeth. When fluoride toothpaste is used, brushing the teeth can help to deliver fluoride to the tooth surfaces, which can help to keep the teeth clean [ 44 , 45 , 46 , 47 ]. The results of the present study suggested that tooth brushing habit is one of the significant factors that can have an effect on the dmft scores of the child.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Relatively recent small-scale studies in Tanzanian adolescents report caries prevalence of 8.8% to 15.0% and mean DMFT of 0.13 (SD = 0.5) to 0.24 (SD = 0.68) in Northern and Southwest Tanzania, respectively. 7 , 8 These studies suggest no obvious increase in caries experience amongst children in Tanzania since the previous national survey report in 2005. 9 …”
Section: Introductionmentioning
confidence: 73%
“… 25 The findings are comparable to many other findings in Tanzania, the African region, and Asia. 7 , 8 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unequal distribution of economic development levels and human resources for oral health is be a major reason for the regional differences in dental caries (13). In addition, other studies show that the dental caries status of 12-year-old adolescents depends on socioeconomic factors (14,15), education in parents (16), and oral hygiene behaviors (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%